Selecting a Monitoring Technology for a Control System of Distributed Oil Production Facilities - Mykhaylo Lobur; Mykola Maliar (Energy Engineering and Control Systems, 2024)
The article proposes the structure of a SCADA system for monitoring and control of oil production facilities that are distributed over a large area. The main emphasis is on the selection of technology that will enable effective monitoring of the equipment of each oil well. Factors such as reliability, ease of use, availability of protection against third-party interference, as well as availability and accessibility of an open-source software code were taken into account. After reviewing the most common software platforms, a system based on Prometheus and Grafana was selected. It is a combination of the Prometheus time series database server and the Grafana information visualization and analysis system. The important factors that determined the choice of this platform were the availability of the open source code and a large library of ready-made templates for displaying the well parameters in real time. An example of the created visualization window of the dynamometer card of the well, built on the basis of the experimentally recorded data, is presented.